Civil Procedure in Montenegro at the End of the 19th and the Beginning of the 20th Century – General Outline - Kulauzov, Maša (Zbornik radova Pravnog fakulteta u Novom Sadu, 2022)
The article sheds light on regulations regarding civil procedure issued in Montenegro at the end of the 19th and the beginning of the 20th century. They deal with various subjects, above all with jurisdiction of civil courts, with deadlines for filing an appeal and with the issue of the finality of judgments as these are the most important questions in civil lawsuits, and, as such, above-mentioned rules were carefully scrutinized in the paper. These first written procedural rules adopted by the Ministry of Justice, the State Council and the Grand Court were very important considering the fact that they introduced modern principles in civil litigations, such as the principles of orality, immediacy, publicity, contradiction, material truth and free judicial evaluation of evidence. However, without the unification of procedural law a speedy and efficient trial and adequate protection of the subjective rights of parties to the proceedings could not be ensured. Only a proper Code of civil procedure could entirely meet these requirements. Montenegrin lawmakers had been fully aware of this fact and so in November 1905 the Code on Judicial Proceedings in Civil Lawsuits for the Principality of Montenegro was enacted. When the aforementioned Code entered into force, the codification endeavor in the field of civil procedural law was completed. Its content, structure and general features were meticulously analyzed in the study.